1997
DOI: 10.1161/01.atv.17.11.3102
|View full text |Cite
|
Sign up to set email alerts
|

Shear Stress Gradients Remodel Endothelial Monolayers in Vitro via a Cell Proliferation-Migration-Loss Cycle

Abstract: Wall shear stress has been implicated in the genesis of atherosclerosis because a strong correlation exists between the location of developing arterial lesions and regions where particular gradients in stress occur. Studying the behavior of endothelial cells in such regions may contribute to our understanding of the disease etiology. We report the detailed migratory history of endothelial cells subjected to large shear stress gradients caused by a surface protuberance in an in vitro model system. The history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
164
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(173 citation statements)
references
References 18 publications
7
164
2
Order By: Relevance
“…Using this in vitro spatial disturbed flow model, dramatic differences in endothelial cell shape, migration, and proliferation have been demonstrated in association with disturbed flow as compared with uniform laminar flow. 34 In addition, significant differences in endothelial expression of Connexin43 at the level of mRNA and protein, and concomitant changes in cell-cell communication via gap junctions, also have been correlated with the presence of shear stress gradients in this model. 35 Recent studies suggest that these in vitro observations may indeed have a counterpart in vivo.…”
mentioning
confidence: 70%
“…Using this in vitro spatial disturbed flow model, dramatic differences in endothelial cell shape, migration, and proliferation have been demonstrated in association with disturbed flow as compared with uniform laminar flow. 34 In addition, significant differences in endothelial expression of Connexin43 at the level of mRNA and protein, and concomitant changes in cell-cell communication via gap junctions, also have been correlated with the presence of shear stress gradients in this model. 35 Recent studies suggest that these in vitro observations may indeed have a counterpart in vivo.…”
mentioning
confidence: 70%
“…Many researchers have investigated pressure, velocity distributions, velocity gradient and the influence of steady and unsteady shear stresses and the gradient of wall shear stress in steady or unsteady flows on the wall or on the blood cell in vascular configurations [9][10][11]. These mechanical factors are involved in the accumulation of lipids, a cause of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that shear stress induces EC monolayer remodeling, e.g., increase of stress fibers and alterations in gene expression (7,8). Shear stress can modulate EC migration in wounding area and vascular stent surface (9)(10)(11)(12), but the kinetics and molecular mechanism of EC migration in response to shear stress remain to be determined.…”
mentioning
confidence: 99%